Facile Method for Obtaining Gold-Coated Polyester Surfaces with Antimicrobial Properties - M. Drobota; M. Butnaru; N. Vornicu; O. Plopa; M. Aflori (Advances in Polymer Technology)
The antimicrobial and antifungal activity of polymers used in medical devices has been extensively studied due to the growing impact of hospital-related infections in patients. The ideal biocidal polymeric materials should be very effective in the microorganism’s inhibition, not toxic to the human body, and environmentally friendly. In this context, this work is aimed at obtaining antimicrobial and antifungal properties at the polyester film surfaces without introducing toxic effects. Poly (ethylene terephthalate) (PET) films were functionalized with Ar plasma and then immersed in a solution containing gold nanoparticles (AuNps). The results demonstrated the appearance of the hydrophilic groups on the film surface after modification of PET film by plasma Ar treatment and the formation of the polar groups such as C=O, COO-, and OH, which then reacted with AuNps. The changes induced in the treated polymer samples were investigated in terms of AuNp adsorption efficiency on polyester film by contact angle, profilometry, Scanning Electron Microscopy (SEM), Attenuated Total Reflectance Spectroscopy-Fourier Transform Infrared (ATR-FTIR), and X-ray Photoelectron Spectroscopy (XPS) measurements. The morphological and structural analyses have shown a good adhesion of AuNps at treated film surfaces. The results of biocompatibility antimicrobial and antifungal tests proved the nontoxic behavior of the sample and its good antimicrobial and antifungal activity.